How NaCl addition destabilizes ionic liquid micellar suspension until phase separation - Dufrêche, Jean-François; Plazanet, Marie; Meyer, Gautier; Billard, Isabelle (Comptes Rendus. Chimie)
The ionic liquid tributyltetradecylphosphonium chloride ([P4,4,4,14]Cl) forms micelles in water, with a very low CMC, below 1 wt%. The solution is macroscopically homogeneous, even large amounts of [P4,4,4,14]Cl in water do not induce any phase separation. The ternary system [P4,4,4,14]Cl/NaCl/H2O instead displays a LCST (Lower Critical Separation Temperature) behavior, being monophasic at low T and experiencing phase separation when T is increased. This phenomenon has been ascribed to the T-increased adsorption onto the micellar surface of these additional chloride ions. The lowering of the repulsive interactions between micelles finally allows coalescence and thus phase separation. In this work, we explore the impact of NaCl addition onto the phase separation, at fixed T. Specific chloride electrode allows the determination of chloride counterion adsorption for different samples in the phase diagram, all of them being single-phase. A simple theory based on the Poisson–Boltzmann equation and with charge regulation is proposed. The only fitted parameter is the chloride adsorption constant. It enables to model the different populations of ions in the solution and at the micelle surface in different conditions. Considering the effective charge of the micelles with respect to the ionic strength of the solution, it moreover provides a key element in the prediction of phase separation.